Methods for detection of horizontal transfer of transposable elements in complete genomes - Carvalho,Marcos Oliveira de (2012)
Recent advances in nucleic acid sequencing technology are creating a diverse landscape for the analysis of horizontal transfer in complete genomes. Previously limited to prokaryotes, the availability of complete genomes from close eukaryotic species presents an opportunity to validate hypotheses about the patterns of evolution and mechanisms that drive horizontal transfer. Many of those methods can be transported from methods previously used in prokaryotic genomes, as the assumptions for horizontal transfer can be interpreted as the same. Some methods, however, require a complete adaptation, while others need refinements in sensitivity and specificity to deal with the huge datasets generated from next-generation sequencing technologies. Here we list the types of methods used for horizontal transfer detection, as well as theirs strengths and weakness.